Hubungan Jumlah Pasien yang Dirawat dengan Tingkat Kelelahan Perawat di Ruang Rawat Inap - Luthfi, Novi; Ahmad, Dalel; Untari, Dewi (Primary Journal of Multidisciplinary Research, 2025)
Work fatigue is one of the common problems experienced by nurses, especially in inpatient wards with high workloads. The number of patients being cared for may affect the level of fatigue, as more patients lead to greater responsibilities for nurses. This study aimed to determine the relationship between the number of patients cared for and the level of nurse fatigue in inpatient wards. This research used a quantitative approach with a cross-sectional design. The sample consisted of 60 nurses working in inpatient wards, selected using purposive sampling. The research instrument was a work fatigue questionnaire that had been tested for validity and reliability. Data were analyzed using the Chi-Square test with a significance level of 0.05. The results showed that most nurses who handled patients beyond the standard ratio experienced moderate to high levels of fatigue. Statistical analysis indicated a significant relationship between the number of patients cared for and the level of nurse fatigue (p < 0.05). This finding suggests that the more patients a nurse cares for, the higher the level of fatigue experienced. In conclusion, the number of patients being cared for has a significant impact on nurse fatigue levels. Therefore, hospital management is expected to consider the nurse-to-patient ratio to maintain service quality and safeguard the health of nurses.